2021
DOI: 10.1007/s10856-021-06615-6
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic differentiation of rat bone mesenchymal stem cells cultured on poly (hydroxybutyrate-co-hydroxyvalerate), poly (ε-caprolactone) scaffolds

Abstract: Bioresorbable biomaterials can fill bone defects and act as temporary scaffold to recruit MSCs to stimulate their differentiation. Among the different bioresorbable polymers studied, this work focuses on poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) and poly(ε-caprolactone) (PCL). Were prepared blends of PHBV and PCL to obtain PHBV based biomaterials with good tenacity, important for bone tissue repair, associated with biocompatible properties of PCL. This study assesses the viability of Vero cells on scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…As an in vitro proof-of-concept on the safety of the HA composite biomaterials, in vitro cytotoxicity and cell viability assays were performed on Vero cell line as they are nonmalignant cells with well-defined culturing characteristics in the experimental settings [ 31 , 32 , 33 ]. Briefly, cells were incubated for 48 h with the different samples; thereafter, their viability was measured and compared to untreated cells.…”
Section: Resultsmentioning
confidence: 99%
“…As an in vitro proof-of-concept on the safety of the HA composite biomaterials, in vitro cytotoxicity and cell viability assays were performed on Vero cell line as they are nonmalignant cells with well-defined culturing characteristics in the experimental settings [ 31 , 32 , 33 ]. Briefly, cells were incubated for 48 h with the different samples; thereafter, their viability was measured and compared to untreated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its appropriate biodegradability and biocompatibility, PHBV has been shown to be a biodegradable biomaterial scaffold used in cartilage tissue engineering and regenerative medicine ( Rodrigues et al, 2021 ). In our previous research, the feasibility of combining CPCs with PHBV to construct tissue-engineered tissues was explored, and we found that the tissue-engineered cartilage on PHBV scaffolds had an insufficient thickness and inadequate biomechanical strength due to the surface hydrophobicity of the scaffold ( Xue et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell localization and distribution on the biomaterial can be analyzed by simply labeling the nuclei at different timepoints after cell seeding on the scaffold [ 52 ]. The morphology of the biomaterial-seeded cells can also be examined by scanning electron microscopy (SEM) [ 14 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], as well as the intracellular structures by transmission electron microscopy (TEM) [ 65 , 68 ]. Cell morphology and distribution can also be assessed using immunofluorescence staining of actin filaments, by means of anti-phalloidin antibodies among others, which allows for the analysis of the cytoskeleton conformation of cell growth in contact with the biomaterials [ 14 , 52 , 54 , 55 , 57 , 60 , 62 , 64 , 65 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Biomaterials Biocompatibilitymentioning
confidence: 99%
“…The relative number of metabolically active cells seeded on the tested biomaterial is usually evaluated by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) colorimetric assay, based on the reduction of the yellow tetrazolium salt MTT to purple formazan crystals by NAD(P)H-dependent oxidoreductase enzymes present in metabolically active cells [ 14 , 56 , 60 , 61 , 65 , 68 , 82 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. The enzyme lactate dehydrogenase (LDH) cytotoxicity assay is another widely used colorimetric assay that allows one to quantify the extracellular concentration of the LDH secreted upon cell damage [ 55 , 83 , 92 , 98 ].…”
Section: Biomaterials Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation